Community readiness assessment for a community-based collecting and archiving project for contemporary komiks - Boquiren, Alain Andrew S. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
Philippine comic books (komiks) have never been taken seriously enough to be properly archived and preserved like other forms of literature. It was the local comic book community who have started an independent practice of promoting, distributing, and preserving komiks during the 2000s, the same decade that local comic book circulation died down. A select few of these nonprofessional practices have started to veer towards community archiving, an archival phenomenon recently recognized by the profession. As of this writing, these would-be community archiving efforts are limited in scope and have yet to develop to involve a larger part of the community.